Ranolazine for Angina in Hypertrophic Cardiomyopathy - Akhtar Amin; Bernard Kim (Case Reports in Cardiology)
Ranolazine is an antianginal and works by inhibiting late-sodium current (INaL). However, its use is limited mostly to patients with coronary artery disease. However, literature has shown its potential benefit in relieving angina in hypertrophic cardiomyopathy. Hereby, we discuss two cases where ranolazine led to improvement in angina refractory to beta-blockers. In conclusion, ranolazine can be considered as a potential antianginal drug in patients with hypertrophic cardiomyopathy refractory to beta-blockers.